101 METASTATIC DUCTAL ECCRINE ADENOCARCINOMA MASQUERADING AS AN INVASIVE DUCTAL CARCINOMA OF THE MALE BREAST. Issue 1 (1st January 2007) - McLean, S. R.; Shousha, S.; Francis, N.; Lim, A.; Eccles, S.; Brock, C. S.; Palmieri, C.
Abstract : We report the case of a 38-year-old male with metastatic ductal eccrine adenocarcinoma (DEA) of the left breast responding to 5-fluorouracil, epirubicin, and cyclophosphamide (FEC) chemotherapy. This patient presented with a 2-week history of difficulty walking due to bilateral hip and lower back pain. Examination revealed an ulcerating cutaneous mass over the left anterior chest wall, left axillary lymphadenopathy, and tenderness over the spine. Investigations, including a punch biopsy of the breast lesion, a CT scan of the thorax, a sonogram of the liver, and a bone scan, were performed, and the patient was originally diagnosed as having metastatic invasive ductal carcinoma (IDC). Radiotherapy was administered to the bony metastases, and he was started on six cycles of FEC chemotherapy. Referral was made to our institution, where the original punch biopsy was reviewed. The tumor cells were polygonal with darkly stained pleomorphic nuclei and abundant eosinophilic cytoplasm and were localized to areas of fibrotic stroma containing eccrine glands and ducts and did not appear to involve mammary tissue. Cells with foamy cytoplasm were observed, a characteristic suggestive of sebaceous gland differentiation. Immunohistochemical studies revealed that the tumor cells were CK7 and GCDFP-15/PIP negative and ERα positive. Both the morphologic and immunohistochemical characteristics of the tumor were consistent with a revised diagnosis of DEA rather than IDC. Symptomatic and radiologic responses to the FEC chemotherapy were subsequently noted. Tamoxifen and ibandronate were given postchemotherapy, and the patient remains pain free 1 year after his original presentation. This case highlights the challenge in discriminating histopathologically between two rare tumors of the male breast, namely DEA and IDC. In addition, clinical response to FEC by metastatic DEA has not been previously documented, and this therapeutic regimen warrants further consideration for the treatment of locally advanced or metastatic DEC.